2005
DOI: 10.1002/humu.20126
|View full text |Cite
|
Sign up to set email alerts
|

Distinct novel mutations affecting the same base in the NIPA1 gene cause autosomal dominant hereditary spastic paraplegia in two Chinese families

Abstract: Hereditary spastic paraplegia (HSP) is a neurodegenerative disease characterized by lower-limb spasticity, hyperreflexia, progressive spastic gait abnormalities, and an extensor-plantar response. It is genetically very heterogeneous, with 28 Human Genome Organisation (HUGO)-approved IDs in the database (last search: August 8, 2004). Following the identification of the SPG6 gene, NIPA1, we have identified two novel mutations, c.316G>C and c.316G>A, in two independent Chinese families linked to the SPG6 locus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…However, one of the families showed a broad range of ageat-onset (ranging between 17 and 40 years) with a much earlier onset observed in younger generations. 2 In contrast, a British SPG6 family demonstrated phenotypic variations between affected family members. In addition, an impression of anticipation was mentioned in the report.…”
Section: Fig 1 Amentioning
confidence: 89%
See 1 more Smart Citation
“…However, one of the families showed a broad range of ageat-onset (ranging between 17 and 40 years) with a much earlier onset observed in younger generations. 2 In contrast, a British SPG6 family demonstrated phenotypic variations between affected family members. In addition, an impression of anticipation was mentioned in the report.…”
Section: Fig 1 Amentioning
confidence: 89%
“…1 To date, two missense mutations, T45R and G106R, were identified in four SPG6 families originating from Irish, Iraqi, Chinese, and British populations. [1][2][3] Here, we report on the clinical and genetic findings of a Brazilian ADHSP family.…”
mentioning
confidence: 96%
“…The T45R mutation occurs at a conserved residue at the interface of the first TM and the first putative outside loop, which would be expected to extend the first TM by three amino acids. More recently, three different research groups identified a missense substitution, G106R, in a number of large unrelated families (14,95,115). The G106R mutation is located in a highly conserved amino acid region within the central portion of the third TM.…”
Section: Strategy For Identifying Novel Mg 2؉ Transportersmentioning
confidence: 99%
“…To date, there has been no systematic genetic and clinical analysis of a large cohort of AD-HSPs in China and only several SPG4 families [10,11,12,13], a few SPG3 families [14,15,16,17]and 3 SPG6 families [17,18 have been] reported. Lin et al [19] mapped the causative gene for an AD-HSP family to 3q24-q26 and revealed that it was caused by a missense mutation in the gene for the acetyl-CoA transporter (SLC33A1) .…”
Section: Introductionmentioning
confidence: 99%